NETWORK HATE SPEECH ON BWF (BADMINTON WORLD FEDERATION) INSTAGRAM ACCOUNTS: FORENSIC LINGUISTIC ANALYSIS - Vinsca Sabrina Claudia; Bagus Juniarto Wibowo (Universitas Sebelas Maret, 2021)
The use of social media is so diverse that it greatly influences the development of communication in society. Currently, netizens are looking for information quickly by using their social media, one of which is Instagram. In general, the use of the media is used to find information as well as communication that contains a lot of hate speech. So, this study aims to describe: (1) the events of implicature speech acts in netizen comments on BWF Instagram, and (2) forms of hate speech in netizen comments on BWF Instagram. The type of research used in this research is descriptive qualitative. The results of this study explain that the event of implicature speech acts with hate speech Indonesian citizens in commenting. Furthermore, the forms of hate speech in comments include illocutionary acts on the types of taboo words, including (1) cursing speech; (2) profanity speech; (3) blashphemy speech; (4) obscenety speech; (5) sexual harassment speech; (6) vulgar language speech, and (7) name-calling and insults speech. The seven utterances were made by Indonesian citizens. Furthermore, this research can be used as an alternative for students of linguistic theory, especially forensic linguistics and pragmatics.